Proceedings of the 25th IMEKO TC4 International Symposium and 23rd International Workshop on ADC and DAC Modelling and Testing 2022
DOI: 10.21014/tc4-2022.28
|View full text |Cite
|
Sign up to set email alerts
|

First results on the functional characterization of two rotary comb-drive actuated MEMS microgripper with different geometry

Abstract: Microgrippers (MGs) are Micro Electro-Mechanical System (MEMS) devices able to manipulate cells and micrometric objects. In order to carry out their functional characterization, a comparison between two electrostatic rotary combdrives actuated prototypes with different geometries through an image analysis-based method is proposed. This study aims at evaluating and comparing the MGs displacement as a function of the supply voltage. The two investigated geometries are equipped with a single rotary comb-drive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that the total number of CSFHs is proportional to the energy necessary to deform the MG structure. As a result, MGs with only one CSFH pair and one pair of electrostatic rotary-comb drives [11][12] demonstrated a wider range of displacement considering the same applied voltage than MGs composed of a double four-bar linkage with multiple CSFHs [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the total number of CSFHs is proportional to the energy necessary to deform the MG structure. As a result, MGs with only one CSFH pair and one pair of electrostatic rotary-comb drives [11][12] demonstrated a wider range of displacement considering the same applied voltage than MGs composed of a double four-bar linkage with multiple CSFHs [13][14].…”
Section: Introductionmentioning
confidence: 99%